ANALISIS STRUKTUR BOX GIRDER JEMBATAN FLY OVER RAWA BUAYA SISI BARAT TERHADAP GEMPA - Aditya Fajar Meidiansyah; M. Yanuar J. Purwanto; Muhammad Fauzan (Departemen Teknik Sipil dan Lingkungan, IPB University, 2016)
The Rawabuaya flyover bridge is an option to overcome the traffic jam that often happens in the Rawabuaya area. It has an extremely vital function to disentangle the traffic congestion; therefore, the structure must be strong in holding the on-going load, specifically the seismic load. The seismic load is dangerous to a structure because it has period that causes the structure to repeatedly shaken. If the movements happened continually, the structure will collapse ― depending on how much earthquake load that is being loaded on the structure. Therefore, it is essential to conduct a structural analysis on the earthquake resistance level of the Rawabuaya flyover bridge based on the